2016
DOI: 10.3325/cmj.2016.57.415
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet in the southern Croatia – does it still exist?

Abstract: AimTo assess the adherence to the Mediterranean diet in the population of Dalmatia in southern Croatia.MethodsA cross-sectional study was performed within the 10 001 Dalmatians cohort, encompassing 2768 participants from Korčula and Vis islands and the City of Split, who were recruited during 2011-2014. Using the data obtained from food frequency questionnaire we calculated the Mediterranean Diet Serving Score (MDSS). Multivariate logistic regression was used to identify the characteristics associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
48
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 39 publications
8
48
1
2
Order By: Relevance
“…Overall, compliance with the Mediterranean diet was rather low in our subjects (23%). As we reported previously, it was particularly low in younger age groups, and lower in men compared to women [17]. Unfortunately, this departure from the traditional Mediterranean diet in the population of Dalmatia represents potentially invaluable losses in the domains of population health, environmental sustainability, local economy and cultural heritage preservation [67].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Overall, compliance with the Mediterranean diet was rather low in our subjects (23%). As we reported previously, it was particularly low in younger age groups, and lower in men compared to women [17]. Unfortunately, this departure from the traditional Mediterranean diet in the population of Dalmatia represents potentially invaluable losses in the domains of population health, environmental sustainability, local economy and cultural heritage preservation [67].…”
Section: Discussionmentioning
confidence: 66%
“…A recent study showed an increase in the prevalence of overweight and obesity from 22.9% in 1999 to 25.0% in 2016 among children aged 2 to 13 years in the Mediterranean part of Europe [15]. One of the explanations for this trend is departure from the traditional lifestyle and Mediterranean diet, especially in younger people from Mediterranean countries [16,17]. Interestingly, it was found that change in the food supply in the Mediterranean area, especially more readily available mass-produced food from the long supply chain (opposite from the local food markets) was associated with MetS [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results indicate that the participants are informed about healthy food choices and their benefits. The confirmation of this statement comes from the results of a similar study which assessed the dietary choices in this population in 2011, 8 years later, and showed a higher level of compliance with the Mediterranean diet, which either implies a positive trend in dietary habits, or at least an even higher level of knowledge concerning healthy nutrition among the participants of the study …”
Section: Discussionmentioning
confidence: 66%
“…It contained six potential answers (every day, 2–3 times a week, once a week, once a month, rarely, never) regarding the frequency of consumption of various foods (milk and dairy products, meat and meat products, fish and fish products, eggs, vegetables, fruit and fruit products, cereals and cereal products, confectionery, and the type of fat used in the preparation of meals). The same FFQ was also used to evaluate the adherence to the Mediterranean diet using the Mediterranean Diet Serving Score (MDSS) method described by Monteagudo et al and used by Kolčić et al for the three Croatian populations. MDSS is an instrument created to assess the Mediterranean diet adherence based on the consumption of 14 groups of foods adding 1, 2 or 3 points based on the consumption frequency and the relative importance of particular foods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation